Drought Impacts and Management - Eyvaz, Murat; Albahnasawi, Ahmed; Tekbaş, Mesut; Gürbulak, Ercan (IntechOpen, 2022)
The deterioration of the balance between precipitation and evaporation and the long duration of this situation is known as drought. Drought adversely affects many environmental components such as soil processes, vegetation growth, wildlife, water quality, and aquatic ecosystems. While drought has unfavorable impacts on both surface and groundwater resources, hydrological regimes can also be affected by it, changing the chemistry of surface waters and the runoff pathway, which can negatively influence water quality. Today one out of every three people is faced with the drought and water shortage risk, thus water scarcity and water stress. This book presents studies on the various forms and severity of the drought that can occur in almost every region of the world as well as their causes and impacts. It analyzes in detail the complex drought phenomenon, which has a significant impact on water resources, agriculture, energy production, human health, and forest fires.